Made to Matter White Fathers, Stolen Generations - Probyn-Rapsey, Fiona (Sydney University Press, 2013)
Most members of the Stolen Generations had white fathers or grandfathers. Who were these white men? This book analyses the stories of white fathers, men who were positioned as key players in the plans to assimilate Aboriginal people by 'breeding out the colour'. The policy was an cruel failure. It conflated skin colour with culture and assumed that Aboriginal women and their children would acquiesce to produce 'future whites'. It also assumed that white men would comply as ready appendages, administering 'whiteness' through marriage or white sperm. This book attempts to put textual flesh on the bodies of these white fathers, and in doing so, builds on and complicates the view of white fathers in this history, and the histories of whiteness to which they are biopolitically related.